Level of Preparedness of Teachers and Pupils in the Era of Technology: A Descriptive Survey - Blessing Chinyere Cleopas (Journal of Technology-Assisted Learning, 2025)
The purpose of the study was to investigate the level of preparedness of teachers and pupils in the era of technology: A descriptive survey research design. The population consisted of all the lower basic schools’ pupils and teachers in two Local Government Areas, Bayelsa State. Twenty-one (21) schools were randomly and purposively selected for the study. A sample size of 100 basic school teachers was drawn from 23 lower basic schools. A 28-item Questionnaire titled, ‘‘Level of Preparedness of Teachers and Pupils for the Era of Technology’’ was used as an instrument for data collection for the study. One research question (What is the level of preparedness of teachers and pupils in the present era of technology?) guided the study. A reliability index of 0.9 was obtained using Cronbach’s alpha computation. The data collected were analyzed using tables, mean, variance, and standard deviation. Findings revealed that technological gadgets that would set the stage rolling for action are not on the ground. Teachers are ready for the integration of technology in the teaching and learning process, but are handicapped due to financial incapacity to meet the needs for quality delivery. Also, most especially, pupils are not prepared for this move due to hunger and the economic incapacitation of their parents. This implied that Nigeria is yet to be ready for the movement of education for the 21st century. Recommendations made include that the government should be committed to addressing the economic state of the nation, boost funding of education, and review the curriculum to suit the requirements of skills and attitude for the 21st century.